Synergy Between the Village Head and Baperkam in the Formulation of Village Regulations in Weriagar Mogotira, Teluk Bintuni Regency - bhynuz_bauw gredhino_jaden (Program Studi Hukum Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to examine the process of formulating village regulations and the constraints encountered in drafting such regulations in Weriagar Mogotira Village, Weriagar District, Teluk Bintuni Regency. The formulation of village regulations by the Village Consultative Body (Baperkam) and the Village Head plays a critical role in producing regulations that conform to the standard procedure of planning, drafting, deliberation, stipulation, and dissemination, all of which must be underpinned by coordination, communication, and synchronization. This research employs a qualitative method to describe the problem under study. Data were collected through direct field observation, interviews, and documentation, and were analyzed using both primary and secondary data to verify the completeness of the information obtained. The findings indicate that Weriagar Mogotira Village does not yet have a village regulation, owing to limited understanding of the mechanism for drafting such regulations. The obstacles identified include a lack of cooperation, instances of disagreement among stakeholders, and the fact that several stakeholders remain unaware of their respective duties and functions; consequently, there is a need to provide the community with a clearer understanding of the duties of the Village Head and Baperkam